Pengaruh Aplikasi Program Pill Time terhadap Tingkat Kepatuhan Pasien Hipertensi di Kelurahan Loktabat Selatan Banjarbaru - Rusida, Esty Restiana; Akbar, Depy Oktapian; Saputra, Mochammad Maulidie Alfianoor; Wati, Helmina; Yanie, A. (BORNEO JOURNAL OF PHARMASCIENTECH, 2026)
One of the diseases experienced by people throughout the region is hypertension. The increase in cases of hypertension is one of the causes of premature death worldwide. Patient compliance in consuming medication can affect the success of hypertension therapy, so appropriate intervention is needed as a recommendation for further therapy to control blood pressure and prevent complications by using appropriate media, easy to use and can be accessed anytime and anywhere using the Pill Time Program Application technology. The of this study was to determine the effect of the Pill Time program application on increasing medication adherence in hypertension patients in South Loktabat Village. This study used a pre-experimental method with a one-group pre-test and post-test design. 99 respondents were selected using simple random sampling. The research data were then analyzed using the Wilcoxon test. The results of the analysis show that the Pill Time program application has an influence on medication adherence in hypertension patients with a Sig. (2-tailed) value of 0.000 < 0.05.